2013
DOI: 10.1002/jgm.2749
|View full text |Cite
|
Sign up to set email alerts
|

Role of endocytic uptake in transfection efficiency of solid lipid nanoparticles‐based nonviral vectors

Abstract: DNA-SLN vector appear to enter productively by multiple pathways in HeLa cells. By contrast, dynamin does not appear to be essential in the productive entry of protamine-containing vectors. In addition, enhancement of the macropinocytic route increases EGFP production when dextran is added to the vector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
(80 reference statements)
0
20
1
1
Order By: Relevance
“…However, we did not observe radical differences, indicating that both pathways would be involved in the uptake of the two including negatively charted PLGA nanoparticles that enter the cell through caveolaeindependent pathways and PEI based cationic polyplexes that utilize CvME have also been reported in the literature 47,51 . In addition, we cannot forget that apart from CME and CvME, clathrin-and caveolae-independent endocytosis routes may also take part in the internalization of the nanoparticles 35,52 . It is worth mentioning that depending on the cell line the internalization pathway of a particular complex could vary.…”
Section: Intracellular Trafficking and Endosomal Escapementioning
confidence: 95%
“…However, we did not observe radical differences, indicating that both pathways would be involved in the uptake of the two including negatively charted PLGA nanoparticles that enter the cell through caveolaeindependent pathways and PEI based cationic polyplexes that utilize CvME have also been reported in the literature 47,51 . In addition, we cannot forget that apart from CME and CvME, clathrin-and caveolae-independent endocytosis routes may also take part in the internalization of the nanoparticles 35,52 . It is worth mentioning that depending on the cell line the internalization pathway of a particular complex could vary.…”
Section: Intracellular Trafficking and Endosomal Escapementioning
confidence: 95%
“…The inhibition resulting from CPZ and glucose suggested that a clathrin-mediated endocytosis pathway was involved in the internalization of the CQDs/pDNA complexes. Moreover, NH 4 Cl was employed due to its ability to neutralize the pH value of endosomal and lysosomal within a very short period to inhibit a low-pH-dependent endosomal escape [51]. The impairment of cellular uptake caused by NH 4 Cl indicated the involvement of endolysosomal trafficking in the internalization of the CQDs/pDNA complexes, which represented a classic consequence of clathrin-mediated endocytosis [64].…”
Section: Investigation Of Cqds Uptakementioning
confidence: 99%
“…To thoroughly investigate the intracellular pathways, eight inhibitors were used to examine the cellular uptake pathways of the CQDs, with chlorpromazine hydrochloride (CPZ) and glucose for inhibiting the clathrindependent endocytosis [49], filipin III and genistein for interfering the caveolae (or caveolae/raft)-mediated endocytosis [50], NH 4 Cl for disturbing the transport of acidic endosomes and lysosomes [51], colchicine for inhibiting the microtubule-dependent active transport [52], SOV for interrupting the cytoskeletal motorsmediated transport [53], and 5-(N,N-dimethyl)-amiloride (DMA) for disturbing the Na + /H + exchange-dependent macropinocytosis [54]. Three different concentrations of each inhibitor were used.…”
Section: Cqds Uptakementioning
confidence: 99%
“…This process has been shown to enhance gene transfection for some cell types by promoting DNA translocation to the nucleus [120, 123]. Other biocompatible molecules such as chitosan and dextran (with protamine) have also been shown to improve transfection for some cell types [114, 124126]. Chloroquine can also be added to the SLN to promote endosome escape and improve transfection efficiency [127].…”
Section: Nps For Retinal Gene Therapymentioning
confidence: 99%